Computational Methods and Experimental Measurements XVI 2013
DOI: 10.2495/cmem130111
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of flow through a wellbore for horizontal wells

Abstract: An understanding of flow in long horizontal wells can be an important aspect of reservoir management. In view of this, a comprehensive study was undertaken for a pipe with a diameter of 0.022 m and two perforations; one on the upper surface and the other on the lower surface with 0.006 m diameter and 180° phasing. The flow variations have been related to geometric and operating parameters. To better understand wellbore flow, Computational Fluid Dynamics CFD simulations (ANSYS CFX-13) have been used to simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The result showed that the pressure drop due to acceleration was significant and equal to 30% of the total pressure and friction pressure drop due to perforation was neglected. Abdulwahid et al [11] provided a numerical simulation model of a pipeline flow with two perforations, one on the upper and one on the lower surface. Using ANSYS to analyse the overall pressure drops, the static pressure, and the average wall shear stress distribution of a horizontal well with a diameter of 22 mm and a length of 1 m. There are two perforations with perforation diameters of 0.006 m and 0.003 m. It is used the RNG (k-ε) model in the plane of symmetry model.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the pressure drop due to acceleration was significant and equal to 30% of the total pressure and friction pressure drop due to perforation was neglected. Abdulwahid et al [11] provided a numerical simulation model of a pipeline flow with two perforations, one on the upper and one on the lower surface. Using ANSYS to analyse the overall pressure drops, the static pressure, and the average wall shear stress distribution of a horizontal well with a diameter of 22 mm and a length of 1 m. There are two perforations with perforation diameters of 0.006 m and 0.003 m. It is used the RNG (k-ε) model in the plane of symmetry model.…”
Section: Introductionmentioning
confidence: 99%
“…To validate the present study, the research of Abdulwahid et al [13] is used. They used CFD to simulate a perforated pipe.…”
Section: Model Validationsmentioning
confidence: 99%
“…Abdulwahid et al [13] analyzed the total pressure, static pressure and wall shear distributions along 1m of horizontal wellbore and diameter of 0.022 m, with two perforations, which the diameter for perforations is 0.006 m and length is 0.003 m, using ANSYS FLUENT and RNG k-ε model in a symmetry plane. Farajpourlar et al [14] studied the major and minor pressure losses, depending on Bernoulli's principle in a single phase gas flow for vertical pipe (with and without perforation) through three images; hydrostatic, frictional and kinetic.…”
Section: Introductionmentioning
confidence: 99%